Behavioral Response of Oyster Valve Gape to Ecological Conditions in an Intermittently Closed Estuary - Niv Anidjar; Sarah N. Giddings; Carlos Neira; George Sugihara; Lisa A. Levin; Kristen A. Goodrich; Jeff Crooks; Duncan Wheeler; Lillian R. McCormick; Luke P. Miller (Estuaries and Coasts, 2026)
Low-inflow estuaries are highly variable and productive habitats. Organisms in these systems must cope with constantly changing conditions. This study investigates the continuous response of oysters to environmental stimuli in a small, low-inflow, estuary, Los Peñasquitos Lagoon (LPL), in San Diego, California, USA. The oysters were placed on a mooring at near-surface and near-bottom locations and instrumented with noninvasive sensors to measure their shell opening (oyster valve gape), concurrently with physical and chemical measurements (water depth, salinity, temperature, dissolved oxygen, pH, solar radiation, wind velocity, and wave radiation stresses) over 136 days. The time series of each oyster with each variable over tidally averaged and shorter time scales were analyzed using traditional statistical methods. The strongest gape relationships were with salinity and dissolved oxygen (Spearman correlation coefficient 0.6), among the oysters near the water surface. Diurnal phase averaging showed how the surface oysters open and close in phase with insolation, while the near-bottom oysters have a lagged response. Tidal phase averaging further illustrates the distinct gape behavior, with surface oysters closing consistently during low tides, and bottom oysters generally remaining open. A subset of variables that had high Spearman correlations (near surface oxygen and salinity, near-bottom pH, solar irradiance, and near-bottom turbidity) and their 18-hour time lags were used to test a set of multivariate models for predicting surface oyster valve gape. The best performing model ( $$r^2 = 0.75$$ ) was consistent with the correlation analysis, showing salinity and dissolved oxygen to be the most important predictors. Key insights from this study are that oysters in LPL have predictable responses to environmental conditions (particularly salinity and dissolved oxygen) with differing responses to conditions near-surface and near-bottom on tidal and tidally-averaged, and faster than tidal timescales.

Chemosynthesis affects benthopelagic trophic coupling and biodiversity in a deep-sea cold seep off Argentina (southwestern Atlantic Ocean) - M. Emilia Bravo; Alejandro A. Tassone; Sebastián Principi; Carola Ferronato; Lisa A. Levin (Journal of Marine Systems, 2026)

Anthropogenic debris accumulation in the Argentine deep sea: evidence of an irreversible sink - Maialen G. Ardusso; Florencia B. Rial; Melisa D. Fernández Severini; Ele Beruschi; Luana Y. Acosta; Andrea N. Álvarez; Juan Cruz Carbajal; Danya Awshah; Xenia Barnes; Lucia Chesta; Moira Décima; Brenda Doti; et al. (Frontiers in Marine Science, 2026)
The seafloor is recognized as a major sink for marine debris, while deep-sea litter remains poorly investigated due to the logistical and economic constraints associated with seabed exploration. This study reports for the first time the occurrence of marine debris found on the Argentine deep seafloor using the SOI’s Remotely Operated Vehicle (ROV), providing the first documented evidence for this region. A total of 29 litter items were recorded across 55.6 km of surveyed seafloor. The highest debris abundance was recorded in submarine canyon areas (1.4 items/km), whereas the Malvinas Basin showed the lowest levels (0.1 items/km), likely associated with hydrodynamic conditions. In addition, plastic items, fishing ropes, and nets were the most frequently recorded types of debris. These findings establish a baseline of the current status of deep-sea marine debris and propose future directions for the region.

Abundant interactions and feedbacks between aquatic deoxygenation and the other planetary boundaries suggest “unsafe” levels of oxygen loss with far‐reaching impacts - Erica M. Ferrer; Yassir A. Eddebbar; Shailja Gangrade; Lillian R. McCormick; Ariel K. Pezner; De'Marcus Robinson; Véronique Garçon; Kevin C. Rose; Lisa A. Levin (Limnology and Oceanography, 2026)
Oxygen is critical for nearly all life on Earth, including aquatic species that breathe dissolved oxygen in both freshwater and marine systems. The rapid, global, and anthropogenic loss of dissolved oxygen known as “aquatic deoxygenation” threatens life in these environments, the human communities that depend on them, and Earth system stability long‐term. Recognizing the important and increasingly widespread effects of aquatic deoxygenation, scientists have proposed that it be added to the planetary boundary framework, which is designed to capture the wider envelope of Earth‐system conditions that support a “safe operating space for humanity.” Here, we argue that the planetary boundary framework should include maintenance of Earth's aquatic ecosystems and thus dissolved oxygen conditions. We synthesize important, in some cases poorly understood, interactions and feedbacks that exist between deoxygenation and all nine of the established planetary boundaries. We find that aquatic deoxygenation interacts with and extensively modulates other boundary processes, including climate change, nutrient loading, biodiversity loss, and aerosol loading. Subsequently, we identify and describe four indicators that can be used to assess the status of aquatic deoxygenation and eventually define a global boundary for it within the framework. Given these interactions and current rates of oxygen loss, we argue that aquatic deoxygenation is approaching an “unsafe space,” with Earth‐system impacts that are likely to be irreversible in our lifetimes. We discuss the wider societal significance of this research, including applications to the framework, future analyses, policy‐making, and management.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

State of deep-sea science and conservation in the Northeast Pacific: implications for policy and management - Fanny Girard; Joan M. Alfaro-Lucas; Amy R. Baco; James P. Barry; Katharine T. Bigham; Lara M. Beckmann; Angelika Brandt; Lindsay Clark; Megan A. Davies; Jeffrey C. Drazen; Anya Dunham; Cherisse Du Preez; et al. (Progress in Oceanography, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Three-dimensional management needs of deep-sea hydrothermal vent ecosystems - Sabine Gollner; Aline Jaeckel; Samantha Robb; Jozée Sarrazin; Verena Tunnicliffe; Jesse M.A. van der Grient; Diva J. Amon; Manuel Bellanger; Catherine Blanchard; Ana Colaço; Cherisse Du Preez; Patricia Esquete; et al. (Marine Policy, 2026)

Hard Rock Buffet: Chemosynthetic Carbon Use and Environmental Trophic Structuring of Carbonate‐Associated Macrofauna at Southern California Methane Seeps - Olívia S. Pereira; Rachel Survilas; María Emilia Bravo; Lisa A. Levin (Marine Ecology, 2026)
Diverse invertebrate communities inhabiting carbonate rocks at methane seeps may rely on a mix of local chemosynthetic production and sinking photosynthetic organic matter, with relative importance shaped by environmental conditions. We investigate the contribution of chemosynthetic carbon to macrofaunal diets at six Southern California methane seeps (275–1020 m depth) and the influence of seep site, seepage habitat, water depth, and oxygen on trophic structure, using stable isotope analyses, Bayesian mixing models, and generalized additive models. Macrofauna exhibit wide isotopic ranges and methane‐derived carbon (MDC) contributions, with several species deriving > 80% of their diet from chemosynthetic sources, including pyropeltid limpets, provannid snails, and dorvilleid and nereidid polychaetes. Negative δ 15 N values and high MDC in a trichobranchid polychaete and sponge are consistent with N 2 fixation or incorporation of N‐fixing microbial biomass. Taxa historically not considered as ‘seep fauna’ (e.g., bryozoans and cnidarians) also incorporate substantial chemosynthetic input, challenging their classification as ‘background’ taxa. Community‐wide trophic structure varied strongly by seep habitat, with active seepage habitats showing higher chemosynthetic reliance, trophic diversity, and isotope ranges. Seep production export into surrounding systems was greater at deeper seeps, suggesting a stronger trophic sphere of seep influence where photosynthetic input is more limited. This increased reliance on chemosynthesis with depth appears to reverse the typical positive δ 15 N‐depth relationship observed in non‐chemosynthetic fauna. Low oxygen seems to favor a restricted number of species with specialized trophic niches. Macrofauna isotopic variability across seep sites likely reflects differences in fluid flux regime and geochemistry. Our study demonstrates that chemosynthetic production plays a broad role in supporting the deep‐sea communities off Southern California and reveals complex, and potentially novel, trophic interactions at methane seeps. These findings underscore the importance of incorporating trophic diversity and associated functional heterogeneity in conservation planning, especially as environmental changes reshape deep‐sea ecosystems, warranting more nuanced protection frameworks.

Megafaunal community structure on ferromanganese and phosphorite hardgrounds in the Southern California Borderland - Devin S. Vlach; Olívia S. Pereira; Francis Nguyen; Angelica Bradley; Kira Mizell; Lisa A. Levin (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Environmental drivers and dynamics of macroinvertebrate communities on carbonates at Southern California methane seeps - Kendra C. Lee; Olívia S. Pereira; Lisa A. Levin (Marine Biology Research, 2025)

Congregation of cusk‐eels ( Genypterus chilensis , Ophidiiformes) at a deep‐sea methane seep off Chile - Lisa A. Levin; Eulogio Soto; Yerko Castillo; Patricia Esquete; Jeffrey Marlow (Ecology, 2025)

Deep Fjords Are Excellent Natural Infrastructure for Climate Impact Studies - Anne Gro Vea Salvanes; Natalya D. Gallo; Martine Røysted Solås; Francesco Saltalamacchia; Dag L. Aksnes; Elin Darelius; Svenja Christiansen; Arild Folkvord; Aino Hosia; Stein Kaartvedt; Lisa Levin; Karin Limburg; et al. (Fish and Fisheries, 2025)
Fjords provide valuable research opportunities for marine scientists. They are excellent natural infrastructure for climate impact studies associated with hypoxic episodes and consequences for mesopelagic and deep‐sea ecosystems involving oceanographic circulation processes and basin water renewals. Repeated sampling from the same populations is possible, making fjords excellent systems for developing time series of data for climate impact studies. We provide an overview of the 14 years of data from Norwegian West Coast fjords, focusing on Masfjorden, and report major findings from Oslofjorden in Eastern Norway, exhibiting recurrent hypoxia in the basin waters. We document that the oxygen levels in Masfjorden decreased rapidly by over 60% at 450 m depth in Periphylla periphylla in view of altered optical conditions of the basin water potentially related to deoxygenation. We argue that fjords like Masfjorden and Oslofjorden are not only macrocosms for ecological processes but also are likely an accelerated version of deep oceans with respect to climate impacts.

High-frequency study of megafaunal communities on whale bone, wood and carbonate in hypoxic Barkley Canyon - Craig R. Smith; Paulo V. F. Correa; Aharon G. Fleury; Lisa A. Levin; Fabio C. De Leo (Frontiers in Marine Science, 2024)
Organic-rich whale bones and wood falls occur widely in the deep sea and support diverse faunal communities, contributing to seafloor habitat diversity. Changes in community structure through succession on deep-sea bone/wood substrates are modulated by ecosystem engineers, i.e., bone-eating Osedax annelids, and wood-boring Xylophaga bivalves. Here, we use a comparative experimental approach and Ocean Networks Canada’s (ONC) cabled observatory in hypoxic Barkley Canyon to study, at high temporal resolution, colonization and succession on whale-bone, Douglas fir wood, and control carbonate rock over 8.3 mo. Experimental substrates were similar in size and mounted on PVC plates near the seafloor at 890 m depth and monitored by high-definition video camera for 5-min intervals every 6-12 h over a period of 8.3 mo. A broad range of seafloor and sea-surface environmental variables were also monitored at this site over the 8.3 mo to account for environmental variability and food input. Following loss of the high-definition camera, substrates were surveyed approximately annually with lower resolution ROV video for an additional 8.5 y. We find that megafaunal abundances, species diversity, and community structure varied substantially over 8.3 mo on each substrate, with markedly different patterns on whale bones due to the development of extensive white bacterial mats. A combination of seafloor and sea surface variables explained < 35% of bone/wood community variation. Bone-eating Osedax annelids failed to colonize whale bones even after 9.2 years, and boring Xylophaga bivalves colonized the wood at much lower rates than in better oxygenated deep-sea locations. Species diversity on whale-bone and wood substrates appeared to be substantially reduced due to the absence of ecosystem engineers and the low oxygen concentrations. We hypothesize that Osedax/Xylophaga colonization, bone/wood degradation, and bone/wood community development may be limited by oxygen concentrations of 0.22 - 0.33 ml.l on the NE Pacific margin, and that OMZ expansion due to climate change will reduce whale-bone and wood degradation, and the contribution of whale falls and wood falls to beta diversity, on the NE Pacific margin.

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Understanding and valuing human connections to deep-sea methane seeps off Costa Rica - Olívia S. Pereira; Mark Jacobsen; Richard Carson; Jorge Cortés; Lisa A. Levin (Ecological Economics, 2024)

Invertebrate trophic structure on marine ferromanganese and phosphorite hardgrounds - Olívia S. Pereira; Devin Vlach; Angelica Bradley; Jennifer Gonzalez; Kira Mizell; Lisa A. Levin (Limnology and Oceanography, 2024)
The Southern California Borderland hosts a variety of geologic and oceanographic features that allow for diverse habitats to occur in a restricted region with a strong oxygen minimum zone (OMZ) and hard substrates. These include ferromanganese (FeMn) crusts and phosphorites targeted for deep‐seabed mining in other regions. Baseline studies regarding hardground macro‐ (> 0.3 mm) and megafaunal (> 2 cm) invertebrates are lacking, although they contribute to understanding nutrient cycling and resilience of deep‐sea communities to ocean deoxygenation, fishing, or mineral extraction. With the goal of understanding how substrate type, depth, and dissolved oxygen concentration influence invertebrate trophic structure, we surveyed δ 13 C and δ 15 N values of invertebrates on hard substrates on the Southern California Borderland margin along a depth gradient (120–2400 m) through the OMZ at inshore ( 15 N increased with decreasing dissolved oxygen and increasing depth, possibly due to remineralization processes within the OMZ and with depth. We discuss how feeding modes and community composition might influence the observed patterns. This study elucidates the importance of the environmental context in shaping invertebrate trophic structure on continental margins and provides baseline knowledge that may be useful in regions where these minerals are targeted for extraction.

Waste barrel contamination and macrobenthic communities in the San Pedro Basin DDT dumpsite - Carlos Neira; Guillermo F. Mendoza; Angelica Bradley; Richard Gossett; Greg W. Rouse; Lisa A. Levin (Marine Pollution Bulletin, 2024)

Consequences of Mouth Closure and Hypoxia-Induced State Changes in Low-Inflow Estuaries: Benthic Community and Trait-Based Response - Lisa A. Levin; Guillermo F. Mendoza; Carlos Neira; Sarah N. Giddings; Jeffrey A. Crooks (Estuaries and Coasts, 2023)
The southern California coastline hosts low-inflow estuaries that have mouths that periodically close. Low-inflow estuaries can become hypoxic and are then often opened mechanically. The consequences of mouth closure and hypoxia (< 2 mg L −1 O 2 ) on macrobenthic densities, species richness, diversity, composition, and biological traits were evaluated for legacy data generated by the Pacific Estuarine Research Lab for Los Peñasquitos Lagoon (LPL) (1991–2006) and Tijuana Estuary (TJE) (1988–2004). LPL closed at least annually and TJE remained open during the study period. Effects were moderated by zone within the estuary (relative to the mouth) and season. Periodic closure in LPL was associated with raised macrofaunal density and diversity, especially at the mouth, and with suppressed seasonality. Closure favored soft-bodied (non-calcified) non-bioturbating, mobile, epifaunal taxa in LPL with planktotrophic development, large branchiae, and no vision. There were more spionid and capitellid polychaetes, Traskorchestia traskiana , Cerithideopsis californica , Tagelus californianus , and phoronids during closure. In contrast, hypoxia (< 2 mg L −1 ) measured during faunal sampling was associated with lower densities in LPL and different taxonomic composition, but no difference in taxon richness or diversity. There were more corophiid amphipods, small snails, tubificid oligochaetes, Palaemon macrodactylus (shrimp), and Trichorixa reticulata (insects) under hypoxic conditions, and retention of taxa with very large or small bodies and with vision. TJE densities were nearly double those of LPL; taxon richness and diversity (H’) were also higher in TJE. TJE hosted more burrowing, large-bodied, highly calcified taxa with planktotrophic development and no vision than LPL. Differences in composition and traits between the two estuaries disappeared in the middle and upper reaches, where ocean flushing was more limited. Historical long-term monitoring data for benthos, such as the data set analyzed here, offer a valuable baseline for evaluating ecosystem response to changes induced by climate, infrastructure development, contamination, or restoration.

Insights from the management of offshore energy resources: Toward an ecosystem-services based management approach for deep-ocean industries - M. Emilia Bravo; Miriam I. Brandt; Jesse M. A. van der Grient; Thomas G. Dahlgren; Patricia Esquete; Sabine Gollner; Daniel O. B. Jones; Lisa A. Levin; Craig R. McClain; Bhavani E. Narayanaswamy; Tracey Sutton; Lissette Victorero; et al. (Frontiers in Marine Science, 2023)
The deep ocean comprises complex ecosystems made up of numerous community and habitat types that provide multiple services that benefit humans. As the industrialization of the deep sea proceeds, a standardized and robust set of methods and metrics need to be developed to monitor the baseline conditions and any anthropogenic and climate change-related impacts on biodiversity, ecosystem function, and ecosystem services. Here, we review what we have learned from studies involving offshore-energy industries, including state-of-the-art technologies and strategies for obtaining reliable metrics of deep-sea biodiversity and ecosystem function. An approach that includes the detection and monitoring of ecosystem services, with open access to baseline data from multiple sectors, can help to improve our global capacity for the management of the deep ocean.

Otoliths of marine fishes record evidence of low oxygen, temperature and pH conditions of deep Oxygen Minimum Zones - Leticia Maria Cavole; Karin E. Limburg; Natalya D. Gallo; Anne Gro Vea Salvanes; Arturo Ramírez-Valdez; Lisa A. Levin; Octavio Aburto Oropeza; Andreas Hertwig; Ming-Chang Liu; Kevin D. McKeegan (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Sexual dimorphism in the methane seep-dwelling Costa Rican yeti crab Kiwa puravida (Decapoda: Anomura: Kiwaidae) - Juan Carlos Azofeifa-Solano; Olívia S. Pereira; Emily Jayne Cowell; Erik E. Cordes; Lisa A. Levin; Shana K. Goffredi; Jorge Cortés (Frontiers in Marine Science, 2022)
Deep-sea chemosynthesis-based ecosystems support unique biological communities, but human impacts are an increasing threat. Understanding the life-history traits of species from deep-sea chemosynthesis-based ecosystems can help to develop adequate management strategies, as these can have impacts on ecological responses to changes in the environment. Here we examined the occurrence of sexual dimorphism in the yeti crab Kiwa puravida , an endemic species from the Costa Rican Pacific margin that aggregates at active methane seeps and depends on chemosynthetic bacteria for nutrition. The two morphological features examined included the claws, suspected to be under sexual selection and used for defense, and the carpus of the second pereopod not suspected to be under sexual selection. A total of 258 specimens, 161 males, 81 females, 16 juveniles, were collected from Mound 12 at 1,000-1,040 m depth in 2017 and 2018 and analyzed. We found that males have larger and wider claws than females, while there were no differences in carpus length. These results suggest that claw weaponry is under sexual selection in K . puravida , which is probably related to the mating system of this deep-sea species. This is the first attempt to study the reproductive biology of K . puravida , and additional observations will be necessary to shed more light on this matter.

Protecting ocean carbon through biodiversity and climate governance - Laura G. Elsler; Maartje Oostdijk; Lisa A. Levin; Erin V. Satterthwaite; Malin L. Pinsky; Guillermo Ortuño Crespo; Mary S. Wisz (Frontiers in Marine Science, 2022)
Global policy goals for halting biodiversity loss and climate change depend on each other to be successful. Marine biodiversity and climate change are intertwined through foodwebs that cycle and transport carbon and contribute to carbon sequestration. Yet, biodiversity conservation and fisheries management seldom explicitly include ocean carbon transport and sequestration. In order to effectively manage and govern human activities that affect carbon cycling and sequestration, international biodiversity and climate agreements need to address both biodiversity and climate issues. International agreements that address issues for climate and biodiversity are best poised to facilitate the protection of ocean carbon with existing policies. The degree to which the main international biodiversity and climate agreements make reference to multiple issues has however not been documented. Here, we used a text mining analysis of over 2,700 binding and non-binding policy documents from ten global ocean-related agreements to identify keywords related to biodiversity, climate, and ocean carbon. While climate references were mostly siloed within climate agreements, biodiversity references were included in most agreements. Further, we found that six percent of policy documents (n=166) included ocean carbon keywords. In light of our results, we highlight opportunities to strengthen the protection of ocean carbon in upcoming negotiations of international agreements, and via area-based management, environmental impact assessment and strategic environmental assessment.

Vulnerability of exploited deep-sea demersal species to ocean warming, deoxygenation, and acidification - William W. L. Cheung; Chih-Lin Wei; Lisa A. Levin (Environmental Biology of Fishes, 2022)

Integrating Multidisciplinary Observations in Vent Environments (IMOVE): Decadal Progress in Deep-Sea Observatories at Hydrothermal Vents - Marjolaine Matabos; Thibaut Barreyre; S. Kim Juniper; Mathilde Cannat; Deborah Kelley; Joan M. Alfaro-Lucas; Valérie Chavagnac; Ana Colaço; Javier Escartin; Elva Escobar; Daniel Fornari; Jörg Hasenclever; et al. (Frontiers in Marine Science, 2022)
The unique ecosystems and biodiversity associated with mid-ocean ridge (MOR) hydrothermal vent systems contrast sharply with surrounding deep-sea habitats, however both may be increasingly threatened by anthropogenic activity (e.g., mining activities at massive sulphide deposits). Climate change can alter the deep-sea through increased bottom temperatures, loss of oxygen, and modifications to deep water circulation. Despite the potential of these profound impacts, the mechanisms enabling these systems and their ecosystems to persist, function and respond to oceanic, crustal, and anthropogenic forces remain poorly understood. This is due primarily to technological challenges and difficulties in accessing, observing and monitoring the deep-sea. In this context, the development of deep-sea observatories in the 2000s focused on understanding the coupling between sub-surface flow and oceanic and crustal conditions, and how they influence biological processes. Deep-sea observatories provide long-term, multidisciplinary time-series data comprising repeated observations and sampling at temporal resolutions from seconds to decades, through a combination of cabled, wireless, remotely controlled, and autonomous measurement systems. The three existing vent observatories are located on the Juan de Fuca and Mid-Atlantic Ridges (Ocean Observing Initiative, Ocean Networks Canada and the European Multidisciplinary Seafloor and water column Observatory). These observatories promote stewardship by defining effective environmental monitoring including characterizing biological and environmental baseline states, discriminating changes from natural variations versus those from anthropogenic activities, and assessing degradation, resilience and recovery after disturbance. This highlights the potential of observatories as valuable tools for environmental impact assessment (EIA) in the context of climate change and other anthropogenic activities, primarily ocean mining. This paper provides a synthesis on scientific advancements enabled by the three observatories this last decade, and recommendations to support future studies through international collaboration and coordination. The proposed recommendations include: i) establishing common global scientific questions and identification of Essential Ocean Variables (EOVs) specific to MORs, ii) guidance towards the effective use of observatories to support and inform policies that can impact society, iii) strategies for observatory infrastructure development that will help standardize sensors, data formats and capabilities, and iv) future technology needs and common sampling approaches to answer today’s most urgent and timely questions.

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

Corrigendum: Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)

Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)
Growing human activity in areas beyond national jurisdiction (ABNJ) is driving increasing impacts on the biodiversity of this vast area of the ocean. As a result, the United Nations General Assembly committed to convening a series of intergovernmental conferences (IGCs) to develop an international legally-binding instrument (ILBI) for the conservation and sustainable use of marine biological diversity of ABNJ [the biodiversity beyond national jurisdiction (BBNJ) agreement] under the United Nations Convention on the Law of the Sea. The BBNJ agreement includes consideration of marine genetic resources (MGR) in ABNJ, including how to share benefits and promote marine scientific research whilst building capacity of developing states in science and technology. Three IGCs have been completed to date with the fourth delayed by the Covid pandemic. This delay has allowed a series of informal dialogues to take place between state parties, which have highlighted a number of areas related to MGR and benefit sharing that require technical guidance from ocean experts. These include: guiding principles on the access and use of MGR from ABNJ; the sharing of knowledge arising from research on MGR in ABNJ; and capacity building and technology transfer for developing states. In this paper, we explain what MGR are, the methods required to collect, study and archive them, including data arising from scientific investigation. We also explore the practical requirements of access by developing countries to scientific cruises, including the sharing of data, as well as participation in research and development on shore whilst promoting rather than hindering marine scientific research. We outline existing infrastructure and shared resources that facilitate access, research, development, and benefit sharing of MGR from ABNJ; and discuss existing gaps. We examine international capacity development and technology transfer schemes that might facilitate or complement non-monetary benefit sharing activities. We end the paper by highlighting what the ILBI can achieve in terms of access, utilization, and benefit sharing of MGR and how we might future-proof the BBNJ Agreement with respect to developments in science and technology.

Eukaryotic Biodiversity and Spatial Patterns in the Clarion-Clipperton Zone and Other Abyssal Regions: Insights From Sediment DNA and RNA Metabarcoding - Franck Lejzerowicz; Andrew John Gooday; Inés Barrenechea Angeles; Tristan Cordier; Raphaël Morard; Laure Apothéloz-Perret-Gentil; Lidia Lins; Lenaick Menot; Angelika Brandt; Lisa Ann Levin; Pedro Martinez Arbizu; Craig Randall Smith; et al. (Frontiers in Marine Science, 2021)
The abyssal seafloor is a mosaic of highly diverse habitats that represent the least known marine ecosystems on Earth. Some regions enriched in natural resources, such as polymetallic nodules in the Clarion-Clipperton Zone (CCZ), attract much interest because of their huge commercial potential. Since nodule mining will be destructive, baseline data are necessary to measure its impact on benthic communities. Hence, we conducted an environmental DNA and RNA metabarcoding survey of CCZ biodiversity targeting microbial and meiofaunal eukaryotes that are the least known component of the deep-sea benthos. We analyzed two 18S rRNA gene regions targeting eukaryotes with a focus on Foraminifera (37F) and metazoans (V1V2), sequenced from 310 surface-sediment samples from the CCZ and other abyssal regions. Our results confirm huge unknown deep-sea biodiversity. Over 60% of benthic foraminiferal and almost a third of eukaryotic operational taxonomic units (OTUs) could not be assigned to a known taxon. Benthic Foraminifera are more common in CCZ samples than metazoans and dominated by clades that are only known from environmental surveys. The most striking results are the uniqueness of CCZ areas, both datasets being characterized by a high number of OTUs exclusive to the CCZ, as well as greater beta diversity compared to other abyssal regions. The alpha diversity in the CCZ is high and correlated with water depth and terrain complexity. Topography was important at a local scale, with communities at CCZ stations located in depressions more diverse and heterogeneous than those located on slopes. This could result from eDNA accumulation, justifying the interim use of eRNA for more accurate biomonitoring surveys. Our descriptions not only support previous findings and consolidate our general understanding of deep-sea ecosystems, but also provide a data resource inviting further taxon-specific and large-scale modeling studies. We foresee that metabarcoding will be useful for deep-sea biomonitoring efforts to consider the diversity of small taxa, but it must be validated based on ground truthing data or experimental studies.

A chemosynthetic ecotone—“chemotone”—in the sediments surrounding deep‐sea methane seeps - Oliver S. Ashford; Shuzhe Guan; Dante Capone; Katherine Rigney; Katelynn Rowley; Victoria Orphan; Sean W. Mullin; Kat S. Dawson; Jorge Cortés; Greg W. Rouse; Guillermo F. Mendoza; Raymond W. Lee; et al. (Limnology and Oceanography, 2021)
Ecotones have been described as “biodiversity hotspots” from myriad environments, yet have not been studied extensively in the deep ocean. While physiologically challenging, deep‐water methane seeps host highly productive communities fueled predominantly by chemosynthetic pathways. We hypothesized that the biological and geochemical influence of methane seeps extends into background habitats, resulting in the formation of a “chemotone” where chemosynthesis‐based and photosynthesis‐based communities overlap. To investigate this, we analyzed the macrofaunal assemblages and geochemical properties of sediments collected from “active,” “transition” (potential chemotone), and “background” habitats surrounding five Costa Rican methane seeps (depth range 377–1908 m). Sediment geochemistry demonstrated a clear distinction between active and transition habitats, but not between transition and background habitats. In contrast, biological variables confirmed the presence of a chemotone, characterized by intermediate biomass, a distinct species composition (including habitat endemics and species from both active and background habitats), and enhanced variability in species composition among samples. However, chemotone assemblages were not distinct from active and/or background assemblages in terms of faunal density, biological trait composition, or diversity. Biomass and faunal stable isotope data suggest that chemotones are driven by a gradient in food delivery, receiving supplements from chemosynthetic production in addition to available photosynthetic‐based resources. Sediment geochemistry suggests that chemosynthetic food supplements are delivered across the chemotone at least in part through the water column, as opposed to reflecting exclusively in situ chemosynthetic production in sediments. Management efforts should be cognisant of the ecological attributes and spatial extent of the chemotone that surrounds deep‐sea chemosynthetic environments.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

University Stormwater Management within Urban Environmental Regulatory Regimes: Barriers to Progressivity or Opportunities to Innovate? - Gregory Pierce; Kyra Gmoser-Daskalakis; Kelsey Jessup; Stanley B. Grant; Andrew Mehring; Brandon Winfrey; Megan A. Rippy; David Feldman; Patricia Holden; Richard Ambrose; Lisa Levin (Environmental Management, 2021)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Extreme temperature events will drive coral decline in the Coral Triangle - Lisa C. McManus; Vítor V. Vasconcelos; Simon A. Levin; Diane M. Thompson; Joan A. Kleypas; Frederic S. Castruccio; Enrique N. Curchitser; James R. Watson (Global Change Biology, 2020)
In light of rapid environmental change, quantifying the contribution of regional‐ and local‐scale drivers of coral persistence is necessary to characterize fully the resilience of coral reef systems. To assess multiscale responses to thermal perturbation of corals in the Coral Triangle (CT), we developed a spatially explicit metacommunity model with coral–algal competition, including seasonal larval dispersal and external spatiotemporal forcing. We tested coral sensitivity in 2,083 reefs across the CT region and surrounding areas under potential future temperature regimes, with and without interannual climate variability, exploring a range of 0.5–2.0°C overall increase in temperature in the system by 2054. We found that among future projections, reef survival probability and mean percent coral cover over time were largely determined by the presence or absence of interannual sea surface temperature (SST) extremes as well as absolute temperature increase. Overall, reefs that experienced SST time series that were filtered to remove interannual variability had approximately double the chance of survival than reefs subjected to unfiltered SST. By the end of the forecast period, the inclusion of thermal anomalies was equivalent to an increase of at least 0.5°C in SST projections without anomalies. Change in percent coral cover varied widely across the region within temperature scenarios, with some reefs experiencing local extinction while others remaining relatively unchanged. Sink strength and current thermal stress threshold were found to be significant drivers of these patterns, highlighting the importance of processes that underlie larval connectivity and bleaching sensitivity in coral networks.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Giant protists (xenophyophores) function as fish nurseries - Lisa A. Levin; Greg W. Rouse (Ecology, 2020)

Meio‐epifaunal wood colonization in the vicinity of methane seeps - Adriana Gracia C.; Lisa A. Levin; Sven Zea (Marine Ecology, 2020)
In deep‐sea environments, plant remains of several origins are found, including branches, twigs, leaves, and wood pieces, among others. As most of the deep‐sea bottoms are oligotrophic and nutrient‐limited, plant remains provide an oasis of localized organic enrichment and a substrate for colonization. Sunken wood was suggested to play an important evolutionary role in the diversification of chemosynthetic ecosystems, possibly representing stepping stones for the colonization between vent and seep ecosystems. In order to understand colonization processes of the Pacific Costa Rican meio‐epifaunal assemblages associated with sunken wood, a field experiment was conducted on Mound 12 (8°55.778′N, 84°18.730′W) at ~1,000 m water depth. Woodblocks were placed in four different habitats (Mussel beds, tube worms, near mussel beds, rubble bottoms), and different local environmental conditions (seepage‐active and seepage‐inactive sites). Seven experimental Douglas fir woodblocks (each 1,047 cm 2 in surface area) were deployed from the R/V Atlantis using the manned submersible Alvin in February 2009 and recovered after 10.5 months in January 2010. Sample processing and analyses led to a data set of abundance (total 9,951 individuals) and spatial distribution of nine meio‐epifaunal higher taxa/groups. Meio‐epifaunal densities on individual woodblocks ranged from 3 to 26 ind.10 cm 2 . Copepods accounted for the highest abundances (75.1%), followed by nauplii larvae (11.7%) and nematodes (9.8%). The maximum number of individuals (26.3 ind.10 cm −2 ) was found in blocks placed in seepage‐inactive areas (near active mussel beds) in contrast to 2.9 ind.10 cm −2 in active areas (within a mussel bed). A hierarchical cluster analysis grouped blocks according to seepage activity and not to habitat, but tests of similarity showed no significant differences in higher taxon composition and abundances, probably owing either to substrate homogeneity or low sample size. Copepods were the most abundant representatives, suggesting that this group is one of the most successful in colonizing in the early stage of succession, in this case while hardwood substrates are not yet decomposed or bored by bivalves.

Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Véronique Garçon; Johannes Karstensen; Artur Palacz; Maciej Telszewski; Tony Aparco Lara; Denise Breitburg; Francisco Chavez; Paulo Coelho; Marcela Cornejo-D’Ottone; Carmen Santos; Björn Fiedler; Natalya D. Gallo; et al. (Frontiers in Marine Science, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Successful Blue Economy Examples With an Emphasis on International Perspectives - Lu Wenhai; Caroline Cusack; Maria Baker; Wang Tao; Chen Mingbao; Kelli Paige; Zhang Xiaofan; Lisa Levin; Elva Escobar; Diva Amon; Yin Yue; Anja Reitz; et al. (Frontiers in Marine Science, 2019)

Sustainability in Deep Water: The Challenges of Climate Change, Human Pressures, and Biodiversity Conservation - Lisa Levin (Oceanography, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Stability and recovery of coral-algae systems: the importance of recruitment seasonality and grazing influence - Lisa C. McManus; James R. Watson; Vítor V. Vasconcelos; Simon A. Levin (Theoretical Ecology, 2019)

Home sweet suboxic home: remarkable hypoxia tolerance in two demersal fish species in the Gulf of California - Natalya D. Gallo; Lisa A. Levin; Maryanne Beckwith; James P. Barry (Ecology, 2019)

Distribution of Meiofauna in Bathyal Sediments Influenced by the Oxygen Minimum Zone Off Costa Rica - Carlos Neira; Jeroen Ingels; Guillermo Mendoza; Elvira Hernandez-Lopez; Lisa A. Levin (Frontiers in Marine Science, 2018)

Response of Sea Urchin Fitness Traits to Environmental Gradients Across the Southern California Oxygen Minimum Zone - Kirk N. Sato; Andreas J. Andersson; James M. D. Day; Jennifer R. A. Taylor; Michael B. Frank; Jae-Young Jung; Joanna McKittrick; Lisa A. Levin (Frontiers in Marine Science, 2018)

Corrigendum: Deep-Sea Mining With No Net Loss of Biodiversity—An Impossible Aim - Holly J. Niner; Jeff A. Ardron; Elva G. Escobar; Matthew Gianni; Aline Jaeckel; Daniel O. B. Jones; Lisa A. Levin; Craig R. Smith; Torsten Thiele; Phillip J. Turner; Cindy L. Van Dover; Les Watling; et al. (Frontiers in Marine Science, 2018)

Deep-Sea Mining With No Net Loss of Biodiversity—An Impossible Aim - Holly J. Niner; Jeff A. Ardron; Elva G. Escobar; Matthew Gianni; Aline Jaeckel; Daniel O. B. Jones; Lisa A. Levin; Craig R. Smith; Torsten Thiele; Phillip J. Turner; Cindy L. Van Dover; Les Watling; et al. (Frontiers in Marine Science, 2018)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Characterization of Methane-Seep Communities in a Deep-Sea Area Designated for Oil and Natural Gas Exploitation Off Trinidad and Tobago - Diva J. Amon; Judith Gobin; Cindy L. Van Dover; Lisa A. Levin; Leigh Marsh; Nicole A. Raineault (Frontiers in Marine Science, 2017)

Colonial Tube-Dwelling Ciliates Influence Methane Cycling and Microbial Diversity within Methane Seep Ecosystems - Alexis L. Pasulka; Shana K. Goffredi; Patricia L. Tavormina; Katherine S. Dawson; Lisa A. Levin; Greg W. Rouse; Victoria J. Orphan (Frontiers in Marine Science, 2017)

Microbial eukaryotic distributions and diversity patterns in a deep‐sea methane seep ecosystem - Alexis L. Pasulka; Lisa A. Levin; Josh A. Steele; David H. Case; Michael R. Landry; Victoria J. Orphan (Environmental Microbiology, 2016)
Summary Although chemosynthetic ecosystems are known to support diverse assemblages of microorganisms, the ecological and environmental factors that structure microbial eukaryotes (heterotrophic protists and fungi) are poorly characterized. In this study, we examined the geographic, geochemical and ecological factors that influence microbial eukaryotic composition and distribution patterns within H ydrate R idge, a methane seep ecosystem off the coast of O regon using a combination of high‐throughput 18S rRNA tag sequencing, terminal restriction fragment length polymorphism fingerprinting, and cloning and sequencing of full‐length 18S rRNA genes. Microbial eukaryotic composition and diversity varied as a function of substrate (carbonate versus sediment), activity (low activity versus active seep sites), sulfide concentration, and region ( N orth versus S outh H ydrate R idge). Sulfide concentration was correlated with changes in microbial eukaryotic composition and richness. This work also revealed the influence of oxygen content in the overlying water column and water depth on microbial eukaryotic composition and diversity, and identified distinct patterns from those previously observed for bacteria, archaea and macrofauna in methane seep ecosystems. Characterizing the structure of microbial eukaryotic communities in response to environmental variability is a key step towards understanding if and how microbial eukaryotes influence seep ecosystem structure and function.

Hydrothermal Vents and Methane Seeps: Rethinking the Sphere of Influence - Lisa A. Levin; Amy R. Baco; David A. Bowden; Ana Colaco; Erik E. Cordes; Marina R. Cunha; Amanda W. J. Demopoulos; Judith Gobin; Benjamin M. Grupe; Jennifer Le; Anna Metaxas; Amanda N. Netburn; et al. (Frontiers in Marine Science, 2016)

Anthropogenic impacts on nitrogen fixation rates between restored and natural Mediterranean salt marshes - Serena Moseman‐Valtierra; Lisa A. Levin; Rose M. Martin (Marine Ecology, 2016)
To test the effects of site and successional stage on nitrogen fixation rates in salt marshes of the Venice Lagoon, Italy, acetylene reduction assays were performed with Salicornia veneta ‐ and Spartina townsendii ‐vegetated sediments from three restored (6–14 years) and two natural marshes. Average nitrogen fixation (acetylene reduction) rates ranged from 31 to 343 μmol C 2 H 4 ·m −2 ·h −1 among all marshes, with the greatest average rates being from one natural marsh (Tezze Fonde). These high rates are up to six times greater than those reported from Southern California Spartina marshes of similar Mediterranean climate, but substantially lower than those found in moister climates of the Atlantic US coast. Nitrogen fixation rates did not consistently vary between natural and restored marshes within a site (Fossei Est, Tezze Fonde, Cenesa) but were negatively related to assayed plant biomass within the acetylene reduction samples collected among all marshes. Highest nitrogen fixation rates were found at Tezze Fonde, the location closest to the city of Venice, in both natural and restored marshes, suggesting possible site‐specific impacts of anthropogenic stress on marsh succession.

Macrobenthos relative to the oxygen minimum zone on the East Indian margin, Bay of Bengal - Akkur V. Raman; Rayaroth Damodaran; Lisa A. Levin; Thiruchitrambalam Ganesh; Yannamani K. V. Rao; Sateesh Nanduri; Rakhesh Madhusoodhanan (Marine Ecology, 2015)
The Bay of Bengal remains one of the least studied of the world's oxygen minimum zones ( OMZ s). Here we offer a detailed investigation of the macrobenthos relative to oxygen minimum zone [ OMZ – DO (dissolved oxygen), concentration −1 ] at 110 stations off the North East Indian margin (16 0 and 20 0 N) featuring coastal, shelf and slope settings (10–1004 m). Macrobenthos (>0.5 mm) composition, abundance and diversity were studied in relation to variations in depth, dissolved oxygen, sediment texture and organic carbon. Using multivariate procedures powered by SIMPROF analysis we identified distinct OMZ core sites (depth 150–280 m; DO 0.37 ml·1 −1 ) that exhibited dense populations of surface‐feeding polychaetes (mean 2188 ind. m −2 ) represented by spionids and cossurids (96%). Molluscs and crustaceans were poorly represented except for ampeliscid amphipods. The lower OMZ sites ( DO > 0.55 ml·l −1 ) supported a different assemblage of polychaetes (cirratulids, amphinomids, eunicids, orbinids, paraonids), crustaceans and molluscs, albeit with low population densities (mean 343 ind. m −2 ). Species richness [E(S 100 )], diversity (Margalef d; H’ ) and evenness (J’) were lower and dominance was higher within the OMZ core region. Multiple regression analysis showed that a combination of sand, clay, organic carbon, and dissolved oxygen explained 62–78% of the observed variance in macrobenthos species richness and diversity: E(S 100 ) and H’ . For polychaetes, clay and oxygen proved important. At low oxygen sites ( DO −1 ), depth accounted for most variance. Residual analysis (after removing depth effects) revealed that dissolved oxygen and sediment organic matter influenced 50–62% of residual variation in E(S 100 ), H’ and d for total macrofauna. Of this, oxygen alone influenced up to ~50–62%. When only polychaetes were evaluated, oxygen and organic matter explained up to 58–63%. For low oxygen sites, organic matter alone had the explanatory power when dominance among polychaetes was considered. Overall, macrobenthic patterns in the Bay of Bengal were consistent with those reported for other upwelling margins. However, the compression of faunal gradients at shallower depths was most similar to the Chile/Peru margin, and different from the Arabian Sea, where the depth range of the OMZ is two times greater. The Bay of Bengal patterns may take on added significance as OMZ s shoal globally.

Methane seep ecosystem functions and services from a recently discovered southern California seep - Benjamin M. Grupe; Monika L. Krach; Alexis L. Pasulka; Jillian M. Maloney; Lisa A. Levin; Christina A. Frieder (Marine Ecology, 2015)
The recent discovery of a methane seep with diverse microhabitats and abundant groundfish in the San Diego Trough (1020 m) off the coast of Del Mar, California raised questions about the role of seep ecosystem functions and services in relation to continental margins. We used multicorer and ROV grab samples and an ROV survey to characterize macrofaunal structure, diversity, and trophic patterns in soft sediments and authigenic carbonates; seep microhabitats and taxa observed; and the abundance and spatial patterns of fishery‐relevant species. Biogenic microhabitats near the Del Mar Seep included microbially precipitated carbonate boulders, bacterial mats, vesicomyid clam beds, frenulate and ampharetid beds, vestimentiferan tubeworm clumps, and fields of Bathysiphon filiformis tubes. Macrofaunal abundance increased and mean faunal δ 13 C signatures decreased in multicorer samples nearer the seep, suggesting that chemosynthetic production enhanced animal densities outside the seep center. Polychaetes dominated sediments, and ampharetids became especially abundant near microbial mats, while gastropods, hydroids, and sponges dominated carbonate rocks. A wide range of stable isotopic signatures reflected the diversity of microhabitats, and methane‐derived carbon was the most prevalent source of nutrition for several taxa, especially those associated with carbonates. Megafaunal species living near the seep included longspine thornyhead ( Sebastolobus altivelis ), Pacific dover sole ( Microstomus pacificus ), and lithodid crabs ( Paralomis verrilli ), which represent targets for demersal fisheries. Sebastolobus altivelis was especially abundant (6.5–8.2 fish·100 m −2 ) and appeared to aggregate near the most active seep microhabitats. The Del Mar Methane Seep, like many others along the world's continental margins, exhibits diverse ecosystem functions and enhances regional diversity. Seeps such as this one may also contribute ecosystem services if they provide habitat for fishery species, export production to support margin food webs, and serve as sinks for methane‐derived carbon.

Geochemical Proxies for Estimating Faunal Exposure to Ocean Acidification - Lisa Levin; Bärbel Hönisch; Christina Frieder (Oceanography, 2015)

And on Top of All That… Coping with Ocean Acidification in the Midst of Many Stressors - Denise Breitberg; Joseph Salisbury; Joan Bernhard; Wei-Jun Cai; Sam Dupont; Scott Doney; Kristy Kroeker; Lisa Levin; W. Chistopher Long; Lisa Milke; Seth Miller; Beth Phelan; et al. (Oceanography, 2015)

Microbial abundance and diversity patterns associated with sediments and carbonates from the methane seep environments of Hydrate Ridge, OR - Jeffrey J. Marlow; Joshua A. Steele; David H. Case; Stephanie A. Connon; Lisa A. Levin; Victoria J. Orphan (Frontiers in Marine Science, 2014)

Alteration of benthic communities associated with copper contamination linked to boat moorings - Carlos Neira; Lisa A. Levin; Guillermo Mendoza; Alberto Zirino (Marine Ecology, 2014)
Although copper ( C u) is an essential element for life, leaching from boat paint can cause excess environmental loading in enclosed marinas. The effects of copper contamination on benthic macrofaunal communities were examined in three S an D iego B ay marinas ( A merica's C up, H arbor I sland W est and E ast) in S outhern C alifornia, USA . The distribution of C u concentration in sediments exhibited a clear spatial gradient, with hotspots created by the presence of boats, which in two marinas exceeded the effect range medium ( ERM ). Elevated sediment C u was associated with differences in benthic assemblages, reduced species richness and enhanced dominance in A merica's C up and H arbor I sland W est, whereas H arbor I sland E ast did not appear to be affected. At sites without boats there were greater abundances of some amphipods such as the species D esdimelita sp., H arpinia sp., A oroides sp., C orophium sp., P odocerus sp., bivalves such as L yonsia californica , M usculista senhousia , M acoma sp., and polychaetes such as D iplocirrus sp. In contrast, at sites with boats, densities of P seudopolydora paucibranchiata , P olydora nuchalis , E uchone limnicola , E xogone lourei , Tubificoides spp. were enhanced. The limited impact on H arbor I sland E ast suggests not only lower C u input rates and increased water flushing and mixing, but also the presence of adequate defense mechanisms that regulate availability and mitigate toxic impacts. At all three marinas, C u in tissues of several macrobenthic species exhibited C u bioaccumulation above levels found in the surrounding environment. The annelids L umbrineris sp. and T ubificoides spp., and the amphipod D esdimelita sp. contained high levels of C u, suggesting they function as C u bioaccumulators. The spionid polychaetes P olydora nuchalis and P seudopolydora paucibranchiata had much lower Cu concentrations than surrounding sediments, suggesting they function as Cu bioregulators. The macrobenthic invertebrates in S an D iego B ay marinas that tolerate C u pollution ( e.g . P . nuchalis, P . paucibranchiata, E uchone limnicola, T yposyllis sp., T ubificoides sp.) may function as indicators of high‐ C u conditions, whereas the presence of C u‐sensitive species ( e.g . P odocerus sp., A oroides sp., H arpinia sp., M acoma sp., L yonsia californica ) may indicate healthier conditions (less C u‐stressed). Parallel responses by faunas of S helter I sland Y acht B asin, also in S an D iego B ay, suggest potential for development of regional C u contamination assessment criteria, and call for functional comparisons with other marinas and coastal water bodies.

New insights on the trophic ecology of bathyal communities from the methane seep area off Concepción, Chile (~36° S) - Germán Zapata‐Hernández; Javier Sellanes; Andrew R. Thurber; Lisa A. Levin; Frédéric Chazalon; Peter Linke (Marine Ecology, 2014)
Studies of the trophic structure in methane‐seep habitats provide insight into the ecological function of deep‐sea ecosystems. Methane seep biota on the Chilean margin likely represent a novel biogeographic province; however, little is known about the ecology of the seep fauna and particularly their trophic support. The present study, using natural abundance stable isotopes, reveals a complex trophic structure among heterotrophic consumers, with four trophic levels supported by a diversity of food sources at a methane seep area off Concepción, Chile (~36° S). Although methanotrophy, thiotrophy and phototrophy are all identified as carbon fixation mechanisms fueling the food web within this area, most of the analysed species (87.5%) incorporate carbon derived from photosynthesis and a smaller number (12%) use carbon derived from chemosynthesis. Methane‐derived carbon ( MDC ) incorporation was documented in 22 taxa, including sipunculids, gastropods, polychaetes and echinoderms. In addition, wide trophic niches were detected in suspension‐feeding and deposit‐feeding taxa, possibly associated with the use of organic matter in different stages of degradation ( e.g . from fresh to refractory). Estimates of Bayesian standard ellipses area (SEA B ) reveal different isotopic niche breadth in the predator fishes, the Patagonian toothfish Dissostichus eleginoides and the combtooth dogfish Centroscyllium nigrum , suggesting generalist versus specialist feeding behaviors, respectively. Top predators in the ecosystem were the Patagonian toothfish D. eleginoides and the dusky cat shark, Bythaelurus canescens . The blue hake Antimora rostrata also provides a trophic link between the benthic and pelagic systems, with a diet based primarily on pelagic‐derived carrion. These findings can inform accurate ecosystem models, which are critical for effective management and conservation of methane seep and adjacent deep‐sea habitats in the Southeastern Pacific.

Can variable pH and low oxygen moderate ocean acidification outcomes for mussel larvae? - Christina A. Frieder; Jennifer P. Gonzalez; Emily E. Bockmon; Michael O. Navarro; Lisa A. Levin (Global Change Biology, 2014)
Natural variation and changing climate in coastal oceans subject meroplanktonic organisms to broad ranges of pH and oxygen ([O 2 ]) levels. In controlled‐laboratory experiments we explored the interactive effects of pH , [O 2 ], and semidiurnal pH fluctuations on the survivorship, development, and size of early life stages of two mytilid mussels, Mytilus californianus and M. galloprovincialis . Survivorship of larvae was unaffected by low pH , low [O 2 ], or semidiurnal fluctuations for both mytilid species. Low pH ( pH was absent when incorporating semidiurnal fluctuations in both species. Also at low pH , larval shells were smaller and had greater variance; this effect was absent when semidiurnal fluctuations of 0.3 units were incorporated at low pH for M. galloprovincialis but not for M. californianus . Low [O 2 ] in combination with low pH had no effect on larval development and size, indicating that early life stages of mytilid mussels are largely tolerant to a broad range of [O 2 ] reflective of their environment (80–260 μ mol kg −1 ). The role of pH variability should be recognized as an important feature in coastal oceans that has the capacity to modulate the effects of ocean acidification on biological responses.

Microbes, macrofauna, and methane: A novel seep community fueled by aerobic methanotrophy - Andrew R. Thurber; Lisa A. Levin; Ashley A. Rowden; Stefan Sommer; Peter Linke; Kerstin Kröger (Limnology and Oceanography, 2013)
During the discovery and description of seven New Zealand methane seep sites, an infaunal assemblage dominated by ampharetid polychaetes was found in association with high seabed methane emission. This ampharetid‐bed assemblage had a mean density of 57,000 ± 7800 macrofaunal individuals m −2 and a maximum wet biomass of 274 g m −2 , both being among the greatest recorded from deep‐sea methane seeps. We investigated these questions: Does the species assemblage present within these ampharetid beds form a distinct seep community on the New Zealand margin? and What type of chemoautotrophic microbes fuel this heterotrophic community? Unlike the other macro‐infaunal assemblages, the ampharetid‐bed assemblage composition was homogeneous, independent of location. Based on a mixing model of species‐specific mass and isotopic composition, combined with published respiration measurements, we estimated that this community consumes 29–90 mmol C m −2 d −1 of methane‐fueled biomass; this is > 290 times the carbon fixed by anaerobic methane oxidizers in these ampharetid beds. A fatty acid biomarker approach supported the finding that this community, unlike those previously known, consumes primarily aerobic methanotrophic bacteria. Due to the novel microbial fueling and high methane flux rates, New Zealand's ampharetid beds provide a model system to study the influence of metazoan grazing on microbially mediated biogeochemical cycles, including those that involve greenhouse gas emissions.

The Dayton legacy: baselines, benchmarks, climate, disturbance and proof - Lisa A. Levin; Maria Cristina Gambi; James P. Barry; Amatzia Genin; Simon Thrush (Marine Ecology, 2011)

The role of cyanobacteria in Southern California salt marsh food webs - Carolyn A. Currin; Lisa A. Levin; Theresa S. Talley; Robert Michener; Drew Talley (Marine Ecology, 2011)
Understanding wetland food webs is critical for effective habitat management, restoration and conservation. Microalgae are recognized as key food sources for marsh invertebrates but the importance of different groups under various conditions is rarely examined. We tested the hypothesis that faunal utilization of microalgae, and cyanobacteria in particular, is significant in Southern California created and natural salt marshes but varies with habitat type (creek bank versus marsh interior) and season (spring versus autumn). We used stable isotope analysis and mixing models (IsoSource) to compare food webs in adjacent young (created) and mature (natural) salt marshes. Isotopic values of some primary producers, macrofauna, epifauna, and fish demonstrated significant differences between the adjacent salt marshes. δ 13 C and δ 34 S values of the benthic microalgal community varied with taxonomic composition (diatoms versus cyanobacteria) and to a lesser extent with season. Depleted δ 15 N values of benthic diatoms and macroalgae indicated that N 2 fixed within algal mats was recycled within the benthic algal community. Marsh fauna, including most major macrofauna taxal, Cerithidea , and Fundulus , also exhibited seasonal differences in isotopic composition, and Cerithidea and selected macrofauna (oligochaetes, polychaetes) from the marsh interior were more enriched in 13 C and depleted in 15 N than those from the creek bank. In the young marsh, the cyanobacteria contributed a minimum of 17–100% of the primary production in food webs supporting macrofauna, and cyanobacteria contributed at least 40% of the primary production included in C e rithidea and Fundulus food webs. A wider range of primary producers contributed to food webs in the mature marsh. Cyanobacteria were a greater source of trophic support for macrofauna from the marsh interior than the creek bank, whereas Spartina was a more important food source for creek bank macrofauna in both marshes. Insect larvae largely consumed cyanobacteria, whereas polychaetes exhibited greater utilization of Spartina . Phytoplankton was the primary food resource for mussels in both marshes. Although the spatial and temporal complexity of food webs has traditionally been collapsed into the study of relatively simplified food webs, isotope signatures reveal fine‐scale patterns in food web structure that may be used to make more accurate assessments of ecosystem state. Accurate interpretation of marsh trophic structure using natural abundance stable isotopes requires fine‐scale resolution in space and time, a large number of samples, and a high level of taxonomic resolution.

The fauna of hydrothermal vents on the Mohn Ridge (North Atlantic) - Christoffer Schander; Hans Tore Rapp; Jon Anders Kongsrud; Torkild Bakken; Jørgen Berge; Sabine Cochrane; Eivind Oug; Ingvar Byrkjedal; Christiane Todt; Tomas Cedhagen; Audun Fosshagen; Andrey Gebruk; et al. (Marine Biology Research, 2010)

Biological structures as a source of habitat heterogeneity and biodiversity on the deep ocean margins - Lene Buhl‐Mortensen; Ann Vanreusel; Andrew J. Gooday; Lisa A. Levin; Imants G. Priede; Pål Buhl‐Mortensen; Hendrik Gheerardyn; Nicola J. King; Maarten Raes (Marine Ecology, 2010)
Biological structures exert a major influence on species diversity at both local and regional scales on deep continental margins. Some organisms use other species as substrates for attachment, shelter, feeding or parasitism, but there may also be mutual benefits from the association. Here, we highlight the structural attributes and biotic effects of the habitats that corals, sea pens, sponges and xenophyophores offer other organisms. The environmental setting of the biological structures influences their species composition. The importance of benthic species as substrates seems to increase with depth as the complexity of the surrounding geological substrate and food supply decline. There are marked differences in the degree of mutualistic relationships between habitat‐forming taxa. This is especially evident for scleractinian corals, which have high numbers of facultative associates (commensals) and few obligate associates (mutualists), and gorgonians, with their few commensals and many obligate associates. Size, flexibility and architectural complexity of the habitat‐forming organism are positively related to species diversity for both sessile and mobile species. This is mainly evident for commensal species sharing a facultative relationship with their host. Habitat complexity is enhanced by the architecture of biological structures, as well as by biological interactions. Colony morphology has a great influence on feeding efficiency for suspension feeders. Suspension feeding, habitat‐forming organisms modify the environment to optimize their food uptake. This environmental advantage is also passed on to associated filter‐feeding species. These effects are poorly understood but represent key points for understanding ecosystems and biodiversity on continental margins. In this paper we explore the contributions of organisms and the biotic structures they create (rather than physical modifications) to habitat heterogeneity and diversity on the deep continental margins.

The roles of habitat heterogeneity in generating and maintaining biodiversity on continental margins: an introduction - Lisa A. Levin; Myriam Sibuet; Andrew J. Gooday; Craig R. Smith; Ann Vanreusel (Marine Ecology, 2010)

Diversity of bathyal macrofauna on the northeastern Pacific margin: the influence of methane seeps and oxygen minimum zones - Lisa A. Levin; Guillermo F. Mendoza; Jennifer P. Gonzalez; Andrew R. Thurber; Erik E. Cordes (Marine Ecology, 2010)
The upper continental slope in the northeastern Pacific Ocean is intercepted by a deep oxygen minimum zone (OMZ; 650–1100 m) and punctuated by conduits of methane seepage. We examined the effects of these two dominant sources of heterogeneity on the density, composition and diversity of heterotrophic macrofauna off Hydrate Ridge, Oregon (OR; 800 m water depth), where the seeps co‐occur within an OMZ, and off the Eel River, Northern California (CA; 500 m), where seeps are overlain by better oxygenated waters. We hypothesized that seeps (containing clam beds and microbial mats) should contribute a suite of distinct species to the regional margin species pool but that OMZ‐associated hypoxia would dampen seep‐related heterogeneity. Macrofaunal densities were highest (23,000–33,510 ind·m −2 ) in the CA seep sediments and in the OR near‐seep samples, intermediate in the OR seep, CA near seep and CA and OR 500‐m margin sediments (10,054–19,777 ind·m −2 ), and lowest in the CA and OR OMZ habitats at 800 m (4269–7847 ind·m −2 ). Annelids constituted over 50% of the taxa in all but the CA clam bed and OR microbial mat sediments, where mollusks were abundant. Approximately 50% of seep species appeared to be habitat endemic; species present in microbial mats largely formed a subset of those present in the clam beds. Dorvilleid and ampharetid polychaetes were dominant in the seep sediments; non‐seep margin sediments at 500 and 800 m were populated heavily by branchiate polychaetes including cossurids and paraonids. Alpha diversity (Es[20] calculated per core) was lowest and rank 1 dominance was highest in the CA and OR microbial mat habitats. Pooled analyses of Es[100] revealed highest species richness in the CA clam bed and near‐seep habitats (30.3 and 29.6, respectively), and lowest species richness in the OR microbial mat and near‐seep habitats (16.5 and 17.9, respectively). Non‐seep sediments (500 and 800 m) off both CA and OR were more homogeneous (55–57% within‐habitat similarity) than clam bed and microbial mat sediments (only 32–37% within‐habitat similarity). CA sediment macrofauna generally exhibit higher alpha diversity, and as habitats are combined, a higher rate of increase in the slope of the species accumulation curves than do OR margin macrofauna. Methane seeps in the NE Pacific introduce significant heterogeneity that increases margin biodiversity at multiple spatial scales. However, our hypothesis that the OMZ would lessen the seep contributions to diversity was not supported. The better oxygenated CA seeps at 500 m shared more of the background margin fauna (at 500 m) than did the OR seeps at 800 m (with OMZ fauna at 800 m). Geographical differences in the fluxes of methane‐rich fluids and the increased reliance on chemosynthetic food sources with increased depth could explain these results.

The influence of geological, geochemical, and biogenic habitat heterogeneity on seep biodiversity - Erik E. Cordes; Marina R. Cunha; Joëlle Galéron; Camilo Mora; Karine Olu‐Le Roy; Myriam Sibuet; Saskia Van Gaever; Ann Vanreusel; Lisa A. Levin (Marine Ecology, 2010)
Cold seeps are among the most heterogeneous of all continental margin habitats. Abiotic sources of heterogeneity in these systems include local variability in fluid flow, geochemistry, and substrate type, which give rise to different sets of microbial communities, microbial symbiont‐bearing foundation species, and associated heterotrophic species. Biogenic habitats created by microbial mats and the symbiotic species including vesicomyid clams, bathymodiolin mussels, and siboglinid tubeworms add an additional layer of complexity to seep habitats. These forms of habitat heterogeneity result in a variety of macrofaunal and meiofaunal communities that respond to changes in structural complexity, habitat geochemistry, nutrient sources, and interspecific interactions in different ways and at different scales. These responses are predicted by a set of theoretical metacommunity models, the most appropriate of which for seep systems appears to be the ‘species sorting’ concept, an extension of niche theory. This concept is demonstrated through predictable patterns of community assembly, succession, and beta‐level diversity. These processes are described using a newly developed analytical technique examining the change in the slope of the species accumulation curve with the number of habitats examined. The diversity response to heterogeneity has a consistent form, but quantitatively changes at different seep sites around the world as the types of habitats present and the size‐classes of fauna analyzed change. The increase in beta diversity across seep habitat types demonstrates that cold seeps and associated biogenic habitats are significant sources of heterogeneity on continental margins globally.

Habitat heterogeneity and its influence on benthic biodiversity in oxygen minimum zones - Andrew J. Gooday; Brian J. Bett; Elva Escobar; Baban Ingole; Lisa A. Levin; Carlos Neira; Akkur V. Raman; Javier Sellanes (Marine Ecology, 2010)
Oxygen minimum zones (OMZs; midwater regions with O 2 concentrations −1 ) are mid‐water features that intercept continental margins at bathyal depths (100–1000 m). They are particularly well developed in the Eastern Pacific Ocean, the Arabian Sea and the Bay of Bengal. Based on analyses of data from these regions, we consider (i) how benthic habitat heterogeneity is manifested within OMZs, (ii) which aspects of this heterogeneity exert the greatest influence on alpha and beta diversity within particular OMZs and (iii) how heterogeneity associated with OMZs influences regional (gamma) diversity on continental margins. Sources of sea‐floor habitat heterogeneity within OMZs include bottom‐water oxygen and sulphide gradients, substratum characteristics, bacterial mats, and variations in the organic matter content of the sediment and pH. On some margins, hard grounds, formed of phosphorites, carbonates or biotic substrata, represent distinct subhabitats colonized by encrusting faunas. Most of the heterogeneity associated with OMZs, however, is created by strong sea‐floor oxygen gradients, reinforced by changes in sediment characteristics and organic matter content. For the Pakistan margin, combining these parameters revealed clear environmental and faunal differences between the OMZ core and the upper and lower boundary regions. In all Pacific and Arabian Sea OMZs examined, oxygen appears to be the master driver of alpha and beta diversity in all benthic faunal groups for which data exist, as well as macrofaunal assemblage composition, particularly in the OMZ core. However, other factors, notably organic matter quantity and quality and sediment characteristics, come into play as oxygen concentrations begin to rise. The influence of OMZs on meiofaunal, macrofaunal and megafaunal regional (gamma) diversity is difficult to assess. Hypoxia is associated with a reduction in species richness in all benthic faunal groups, but there is also evidence for endemism in OMZ settings. We conclude that, on balance, OMZs probably enhance regional diversity, particularly in taxa such as Foraminifera, which are more tolerant of hypoxia than others. Over evolutionary timescales, they may promote speciation by creating strong gradients in selective pressures and barriers to gene flow.

Diversity and functional responses of nitrogen-fixing microbes to three wetland invasions - Serena M. Moseman; Rui Zhang; Pei Yuan Qian; Lisa A. Levin (Biological Invasions, 2009)

Utilization of invasive tamarisk by salt marsh consumers - Christine R. Whitcraft; Lisa A. Levin; Drew Talley; Jeffrey A. Crooks (Oecologia, 2008)

Marine Metapopulations - Celeste Benham; Alison M. Cawood; Geoffrey S. Cook; Ange Darnell; Peter C. Davison; Miriam C. Goldstein; Ayana Elizabeth Johnson; Talina Konotchick; Elisa M. Maldonado; Alexis L. Pasulka; Jennifer C. Prairie; Serena M. Moseman; et al. (Marine Ecology, 2008)

Linking juvenile habitat utilization to population dynamics of California halibut - F. Joel Fodrie; Lisa A. Levin (Limnology and Oceanography, 2008)
We investigated the nursery role of four coastal ecosystems for the California halibut (Paralichthys californicus) using the following metrics: (1) contribution in producing the fish that advance to older age classes, (2) connectivity of coastal systems resulting from migration of fish from juvenile to subadult habitats, and (3) effect of nursery habitat usage and availability on subadult population size, specifically evaluating the concentration hypothesis. Potential nurseries were grouped using a robust classification scheme that segregated exposed, bay, lagoon, and estuarine environments. Assignment of nursery origins for individual subadult fish via elemental fingerprinting indicated that exposed coasts, bays, lagoons, and estuaries contributed 31%, 65%, 1%, and 3% of advancing juvenile halibut during 2003, versus 49%, 33%, 16%, and 2% during 2004, respectively. These results were remarkably similar to “expected” nursery contributions derived from field surveys, suggesting that in this system juvenile distributions were a good indicator of unit‐area productivity of juvenile habitats and that densitydependent mechanisms during the juvenile phase did not regulate recruitment pulses. Elemental fingerprinting also demonstrated that individuals egressing from bays did not migrate far from their nursery origins (

Influence of invasive Spartina growth stages on associated macrofaunal communities - Carlos Neira; Lisa A. Levin; Edwin D. Grosholz; Guillermo Mendoza (Biological Invasions, 2007)

Concerns and recommendations regarding inherited cancer risk: The perspectives of survivors and female relatives - Suzanne Mellon; Lisa Berry-Bobovski; Robin Gold; Nancy Levin; Michael A. Tainsky (Journal of Cancer Education, 2007)

Population Connectivity and Larval Dispersal Using Geochemical Signatures in Calcified Structures - Simon Thorrold; Danielle Zacherl; Lisa Levin (Oceanography, 2007)

Extreme food webs: Foraging strategies and diets of scavenging amphipods from the ocean’s deepest 5 kilometers - Lesley E. Blankenship; Lisa A. Levin (Limnology and Oceanography, 2007)
We explore hypotheses that alternate foraging strategies, diet, or nutrient partitioning could help explain the success of scavenging Lysianassoids (Amphipoda) in hadal oligotrophic trenches (depths of 6–11 km) by examining the nutritional strategies of four lysianassoid species ( Eurythenes gryllus , Scopelocheirus schellenbergi , Hirondellea dubia , and Uristes sp. nov.) collected with baited traps (6.3‐10.8 km) from the oligotrophic Tonga and Kermadec Trenches (southwest Pacific Ocean). Diets and foraging strategies were examined by use of (1) the nascent DNA‐based analysis of hindgut contents, which provides a ‘snapshot’ of recently ingested organisms, and (2) natural abundance isotopic signatures, which reflect the source of nutrition and relative trophic position. The scavenging guild exhibits remarkable trophic plasticity, and each amphipod species employs alternate foraging modes, including detrivory or predation, to supplement necrophagy. The nutritional strategies of some species appear to shift with age, depth, and even between trenches. Thus, there is no single ubiquitous hadal food web; rather it is influenced by depth and overlying surface productivity. Isotopic data suggest that coexisting species partition the dietary items, providing evidence of competition among members of the scavenging guild. The extreme foraging flexibility of scavenging amphipods may ultimately contribute to their success in severely foodlimited hadal ecosystems.

Oxygen as a control on sea floor biological communities and their roles in sedimentary carbon cycling - Clare Woulds; Greg L. Cowie; Lisa A. Levin; Johan H. Andersson; Jack J. Middelburg; Sandra Vandewiele; Peter A. Lamont; Kate E. Larkin; Andrew J. Gooday; Stefanie Schumacher; Christine Whitcraft; Rachel M. Jeffreys; et al. (Limnology and Oceanography, 2007)
13 C tracer experiments were conducted at sites spanning the steep oxygen, organic matter, and biological community gradients across the Arabian Sea oxygen minimum zone, in order to quantify the role that benthic fauna play in the short‐term processing of organic matter (OM) and to determine how this varies among different environments. Metazoan macrofauna and macrofauna‐sized foraminiferans took up as much as 56 ± 13 mg of added C m −2 (685 mg C m −2 added) over 2–5 d, and at some sites this uptake was similar in magnitude to bacterial uptake and/or total respiration. Bottom‐water dissolved oxygen concentrations exerted a strong control over metazoan macrofaunal OM processing. At oxygen concentrations −1 (0.16 ml L −1 ), metazoan macrofauna were able to take advantage of abundant OM and to dominate OM uptake, while OM processing at O 2 concentrations of 5.0 µmol L −1 (0.11 ml L −1 ) was dominated instead by (macrofaunal) foraminiferans. This led us to propose the hypothesis that oxygen controls the relative dominance of metazoan macrofauna and foraminifera in a threshold manner, with the threshold lying between 5 and 7 µmol L −1 (0.11 to 0.16 ml L −1 ). Large metazoan macrofaunal biomass and high natural concentrations of OM were also associated with rapid processing of fresh OM by the benthic community. Where they were present, the polychaete Linopherus sp. and the calcareous foraminiferan Uvigerina ex gr. semiornata , dominated the uptake of OM above and below, respectively, the proposed threshold concentrations of bottom‐water oxygen.

Novel Antifoulants: Inhibition of Larval Attachment by Proteases - Sergey Dobretsov; Hairong Xiong; Ying Xu; Lisa A. Levin; Pei-Yuan Qian (Marine Biotechnology, 2007)

Succession of microphytobenthos in a restored coastal wetland - Christopher N. Janousek; Carolyn A. Currin; Lisa A. Levin (Estuaries and Coasts, 2007)

Advances in Vent, Seep, Whale‐ and Wood‐Fall Biology - Lisa A. Levin; James P. Barry; Horst Felbeck; Craig R. Smith; Craig M. Young (Marine Ecology, 2007)

Community structure and nutrition of deep methane‐seep macrobenthos from the North Pacific (Aleutian) Margin and the Gulf of Mexico (Florida Escarpment) - Lisa A. Levin; Guillermo F. Mendoza (Marine Ecology, 2007)
Methane seeps occur at depths extending to over 7000 m along the world's continental margins, but there is little information about the infaunal communities inhabiting sediments of seeps deeper than 3000 m. Biological sampling was carried out off Unimak Island (3200–3300 m) and Kodiak Island (4500 m) on the Aleutian margin, Pacific Ocean and along the Florida Escarpment (3300 m) in the Gulf of Mexico to investigate the community structure and nutrition of macrofauna at these sites. We addressed whether there are characteristic infaunal communities common to the deep‐water seeps or to the specific habitats (clam beds, pogonophoran fields, and microbial mats) studied here, and ask how these differ from background communities or from shallow‐seep settings sampled previously. We also investigated, using stable isotopic signatures, the utilization of chemosynthetically fixed and methane‐derived organic matter by macrofauna from different regions and habitats. Within seep sites, macrofaunal densities were the greatest in the Florida microbial mats (20,961 ± 11,618 ind·m −2 ), the lowest in the Florida pogonophoran fields (926 ± 132 ind·m −2 ), and intermediate in the Unimak and Kodiak seep habitats. Seep macrofaunal densities differed from those in nearby non‐seep sediments only in Florida mat habitats, where a single, abundant species of hesionid polychaete comprised 70% of the macrofauna. Annelids were the dominant taxon (>60%) at all sites and habitats except in Florida background sediments (33%) and Unimak pogonophoran fields (27%). Macrofaunal diversity (H′) was lower at the Florida than the Alaska seeps, with a trend toward reduced richness in clam bed relative to pogonophoran field or non‐seep sediments. Community composition differences between seep and non‐seep sediments were evident in each region except for the Unimak margin, but pogonophoran and clam bed macrofaunal communities did not differ from one another in Alaska. Seep δ 13 C and δ 15 N signatures were lighter for seep than non‐seep macrofauna in all regions, indicating use of chemosynthetically derived carbon. The lightest δ 13 C values (average of species’ means) were observed at the Florida escarpment (−42.8‰). We estimated that on average animal tissues had up to 55% methane‐derived carbon in Florida mats, 31–44% in Florida clam beds and Kodiak clam beds and pogonophoran fields, and 9–23% in Unimak seep habitats. However, some taxa such as hesionid and capitellid polychaetes exhibited tremendous intraspecific δ 13 C variation (>30‰) between patch types. Overall we found few characteristic communities or features common to the three deep‐water seeps (>3000 m), but common properties across habitats (mat, clam bed, pogonophorans), independent of location or water depth. In general, macrofaunal densities were lower (except at Florida microbial mats), community structure was similar, and reliance on chemosynthesis was greater than observed in shallower seeps off California and Oregon.

The role of transitional areas as avian biodiversity centres - Salit Kark; Thomas F. Allnutt; Noam Levin; Lisa L. Manne; Paul H. Williams (Global Ecology and Biogeography, 2007)
Aim With the ever‐increasing threats to biodiversity, efforts are being directed towards identifying hotspots of special importance for conservation. In particular, there has been an effort to identify irreplaceable regions that are especially rich in rare species. Areas of transition between ecological systems in which multiple species coincide are expected, almost by definition, to be species‐rich. Here, we examine whether this is simply a result of an overlap between two communities in boundary regions, or whether boundary areas also hold concentrations of rare (e.g. range‐limited) species. We ask whether an analysis that includes areas of transition may be a useful contribution to the identification of biodiversity centres. Location and methods To address these questions, we examined the relationship between passeriform richness and range size rarity of approximately 2300 bird species in 4889 1° New World grid cells, and the distance of the cells to boundaries between adjacent plant‐based ecoregions. Results Areas nearer to boundary regions between ecoregions not only had more bird species, but also scored more highly in terms of species rarity. The range centres of the rarest 10% of species were distributed significantly closer to boundaries between ecoregions than were species in general. This pattern persisted for rarity when we divided the New World into three latitudinal belts and analysed each separately, and when we excluded the Andes. It also persisted when compared with randomly generated ecoregion polygons. Main conclusions The findings of this work suggest that transitional environments harbour many rare species, in addition to high richness. Consequently areas of biotic transition should be highly valued as biodiversity centres and need to be included in future global conservation analyses and decisions.

The role of transitional areas as avian biodiversity centres - Salit Kark; Thomas F. Allnutt; Noam Levin; Lisa L. Manne; Paul H. Williams (Global Ecology and Biogeography, 2006)

Kristian Fauchald: A Tribute - Greg W. Rouse; Maria Cristina Gambi; Lisa A. Levin (Marine Ecology, 2005)

‘Back to the future’ - Maria Cristina Gambi; Lisa Ann Levin (Marine Ecology, 2005)

Surficial Hydrocarbon Seep Infauna from the Blake Ridge (Atlantic Ocean, 2150 m) and the Gulf of Mexico (690–2240 m) - Christie A. Robinson; Joan M. Bernhard; Lisa A. Levin; Guillermo F. Mendoza; Jessica K. Blanks (Marine Ecology, 2004)
Infauna, including foraminifera and metazoans, were enumerated and identified from five types of seep habitats and two adjacent non‐seep habitats. Collections were made with the deep submergence research vessel ‘Alvin’ from three areas of active seepage in the Gulf of Mexico (Alaminos Canyon [2220 m], Atwater Canyon [1930 m], and Green Canyon lease block 272 [700 m]) and on the Blake Ridge Diapir [2250 m], which is located off the southeastern coast of the United States. The seep habitats sampled included four types of microbial mats ( Beggiatoa , Thioploca , thin and thick Arcobacter ) and the periphery of a large mussel bed. Sediments under large rhizopod protists, xenophyophores, were sampled adjacent to the mussel bed periphery. A non‐seep site, which was >1 km away from active seeps, was also sampled for comparison. Densities of most taxa were higher in the Gulf of Mexico seeps than in Blake Ridge samples, largely because densities in the thick microbial mats of Blake Ridge were significantly lower. Diversity was higher in the Thioploca mats compared to other microbial‐mat types. Within an ocean basin ( i.e. , Atlantic, Gulf of Mexico) we did not observe significant differences in meiofaunal or macrofaunal composition in Beggiatoa versus Thioploca mats or thin versus thick Arcobacter mats. Foraminifera represented up to 16% of the seep community, a proportion that is comparable to their contribution at adjacent non‐seep communities. In general, the observed densities and taxonomic composition of seep sites at the genus level was consistent with previous observations from seeps ( e.g. , the foraminifers Bolivina and Fursenkoina , the dorvilleid polychaete Ophryotrocha ).

Isotopic evidence for chemosynthesis‐based nutrition of macrobenthos: The lightness of being at Pacific methane seeps - Lisa A. Levin; Robert H. Michener (Limnology and Oceanography, 2002)
The importance of chemosynthetic nutritional pathways was examined for macrofaunal invertebrates (≫300 µm) from methane seeps in the Gulf of Alaska (4,413–4,443 m), on the Oregon margin (590 m), and on the northern California slope [Eel River margin] (520 m) by use of natural abundance stable isotopic data. Seep macrofauna exhibited lighter Δ 13 C and Δ 15 N values than those in nonseep sediments, but isotopic signatures varied among seep sites. Macrofaunal isotopic signatures indicated chemosynthetically fixed carbon sources with a significant contribution from methane‐derived carbon (MDC) in macrofauna from sediments of pogonophoran fields (average Δ 13 C, 246.44‰, 32%–51% MDC) and Calyptogena phaseoliformis beds (average Δ 13 C, 240.89‰, 12%–40% MDC) in the Gulf of Alaska and in microbial mat sediments on the Oregon margin (average Δ 13 C, 243.80‰, 20%–44% MDC). Lesser influence of MDC was noted in macrofauna from sediments of Calyptogena pacifica beds on the Oregon (average Δ 13 C, 233.38‰, 0%–27% MDC) and California ( Δ 13 C, 225.10‰, 0%‐22% MDC) margins and from California microbial mat sediments ( Δ 13 C, 222.23‰, 0%–5% MDC). Although most macrofauna appeared to be heterotrophic, light Δ 15 N and Δ 13 C values together provided evidence for chemoautotrophic symbioses in selected taxa. Carbon isotopic signatures were consistent with consumption of methane‐oxidizing archaea by some dorvilleid polychaetes (Δ 13 C, 290.62‰ and 273.80‰) and with grazing on filamentous sulfur bacteria by gastropods and polychaetes from the Oregon and California seeps. The importance of chemosynthetic trophic pathways varies regionally and among microhabitats, taxonomic groups, and feeding guilds.

Managing Critical Transition Zones - Katherine C. Ewel; Claudia Cressa; Ronald T. Kneib; P. S. Lake; Lisa A. Levin; Margaret A. Palmer; Paul Snelgrove; Diana H. Wall (Ecosystems, 2001)

The Function of Marine Critical Transition Zones and the Importance of Sediment Biodiversity - Lisa A. Levin; Donald F. Boesch; Alan Covich; Cliff Dahm; Christer Erséus; Katherine C. Ewel; Ronald T. Kneib; Andy Moldenke; Margaret A. Palmer; Paul Snelgrove; David Strayer; Jan Marcin Weslawski (Ecosystems, 2001)

Development and application of elemental fingerprinting to track the dispersal of marine invertebrate larvae - Claudio DiBacco; Lisa A. Levin (Limnology and Oceanography, 2000)
The early life history of many marine benthic invertebrate and fish species involves a planktonic larval stage that allows exchange of individuals among separated adult populations. Here, we demonstrate how natural and anthropogenic trace elements can be used to determine larval origins and assess bay‐ocean exchange of invertebrate larvae. Trace elements can be effective site markers for estuaries because run‐off and pollutant loading often impart distinct elemental signatures to bay habitats relative to nearshore coastal environments. Crab larvae originating from San Diego Bay (SDB) were distinguished from those originating in neighboring embayments and exposed coastal habitats by comparing multiple trace‐element concentrations (“fingerprint”) in individuals. Discriminant function analysis (DFA) was used to characterize stage I zoeae of the striped shore crab, Pachygrapsus crassipes , of known origin (reference larvae) via trace‐elemental composition (i.e., Cu, Zn, Mn, Sr, Ca). Linear discriminant functions were used to identify the origin and characterize the exchange of stage I P. crassipes zoeae between SDB and the nearshore coastal environment during one spring tidal cycle. Elemental fingerprinting revealed that most (87%) of the stage I larvae collected at the bay entrance during the flood tide were larvae of SDB origin that were reentering the bay. Nearly one third of zoeae sampled (32%) at the entrance during ebb tide were coastal larvae leaving the bay and returning to open water. The observed bidirectional exchange contrasts with the unidirectional transport of zoeae out of the bay predicted from stage I vertical migratory behavior. Because P. crassipes zoeal survivorship is lower in SDB than in coastal waters, bay‐ocean exchange has significant implications for the dynamics of P. crassipes populations. Trace‐elemental fingerprinting of invertebrate larvae promises to facilitate investigations of many previously intractable questions about larval transport and dynamics.